2020
DOI: 10.1038/s41467-020-14374-1
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting glutamine metabolism slows soft tissue sarcoma growth

Abstract: Tumour cells frequently utilize glutamine to meet bioenergetic and biosynthetic demands of rapid cell growth. However, glutamine dependence can be highly variable between in vitro and in vivo settings, based on surrounding microenvironments and complex adaptive responses to glutamine deprivation. Soft tissue sarcomas (STSs) are mesenchymal tumours where cytotoxic chemotherapy remains the primary approach for metastatic or unresectable disease. Therefore, it is critical to identify alternate therapies to improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 70 publications
(107 reference statements)
5
57
0
Order By: Relevance
“…Despite the promising cell proliferation inhibition results observed in vitro, some cancer cells show resistance to glutaminase inhibitors. More importantly, the in vivo data of glutaminase inhibition is still quite limited and shows controversial results (42,130,135). Gross et al reported significant antitumor activities of CB-839 in two xenograft models, a patient-derived TNBC model and a basal like HER2+ cell line model (JIMT-1) (42).…”
Section: Glutaminase Inhibitor Based Therapeutic Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the promising cell proliferation inhibition results observed in vitro, some cancer cells show resistance to glutaminase inhibitors. More importantly, the in vivo data of glutaminase inhibition is still quite limited and shows controversial results (42,130,135). Gross et al reported significant antitumor activities of CB-839 in two xenograft models, a patient-derived TNBC model and a basal like HER2+ cell line model (JIMT-1) (42).…”
Section: Glutaminase Inhibitor Based Therapeutic Strategymentioning
confidence: 99%
“…Gross et al reported significant antitumor activities of CB-839 in two xenograft models, a patient-derived TNBC model and a basal like HER2+ cell line model (JIMT-1) (42). Lee et al reported a successful inhibition of undifferentiated pleomorphic sarcoma (UPS) tumor growth with CB-839 (135). Combination therapy of CB-839 and PARP inhibitor olaparib also showed prolonged survival in a xenograft model of ovarian cancer (136).…”
Section: Glutaminase Inhibitor Based Therapeutic Strategymentioning
confidence: 99%
“…Glucose is a raw material that makes up various biological substances, but it contains only carbon, hydrogen, and oxygen. Since glutamine plays an important role as a source of nitrogen in amino acids and nucleic acids, it is known that many cancer cells have a high dependence on glutamine [ 66 , 67 , 68 , 69 , 70 ]. Glutamine uptake and metabolism in cancer cells is regulated by PI3K, Kras, and c-myc [ 26 , 43 , 66 , 67 , 71 , 72 , 73 , 74 , 75 ].…”
Section: Tumor Metabolismmentioning
confidence: 99%
“…mTORC1 has a central role in the metabolic regulation of cancer cells, so metformin may enhance the effects of other metabolic inhibitors by inhibiting the metabolic reprograming of CSCs. The glutaminase inhibitors BPTES and CB839 strongly inhibit the growth of glutamine-addicted tumors even when used alone, but they have been shown to be more potent when combined with other metabolic inhibitors or conventional chemotherapy [ 68 , 69 , 70 , 171 , 178 , 179 ]. The FAO inhibitor etomoxir also enhanced the therapeutic effect of conventional chemotherapy in several types of cancers in vivo [ 138 , 180 , 181 ].…”
Section: Therapeutic Strategies For Targeting Csc Metabolismmentioning
confidence: 99%
“…After MUC1 was knocked out in pancreatic cancer cells, Fu et al found that the metabolic activity of the cancer cells was significantly reduced, the cancer cells were better able to receive chemotherapy [27]. Similarly, in soft tissue sarcoma, targeting glutamine metabolism can well inhibit tumor growth [28]. Drugs that inhibit glucose metabolism and drugs that inhibit lipid metabolism can be used as a new treatment for lung cancer [29].…”
Section: Discussionmentioning
confidence: 99%